Tax Aspects of Mergers and Cross-Border Mergers - Marcela Žárová; Jana Skálová (European Financial and Accounting Journal, 2014)
The paper concentrates on tax aspects of merger with a special attention to cross-border ones. Despite the fact that Directive, which set the conditions for mergers, business investment and exchange rate of shares, was issued 24 years ago, unified treatment of tax aspects hasnt been reached yet. This paper is based on research of tax rules transposed from Tax Merger Directive, 83 into law systems of EU member states. This Directive was used for tax treatment of domestic mergers as for cross-border ones. Although the Directive has been transposed, there are differences in tax treatment among member states. The paper shows inability of solving the problem by Directive as coordination of the tax and legal regime of several jurisdictions are usually not adapted to each other and examples when the European Court of Justice is asked for treatment. Different approaches to discussed issues are presented in the paper.
Keywords: H25; H32; 650; Tax aspects; Take over losses; Cross-border mergers